2017
DOI: 10.1002/hyp.11092
|View full text |Cite
|
Sign up to set email alerts
|

Modeling discharge and sediment concentrations after landscape interventions in a humid monsoon climate: The Anjeni watershed in the highlands of Ethiopia

Abstract: Increasing population and intensification of agriculture increase erosion rates and often result in severe land degradation and sedimentation of reservoirs. Finding effective management practices to counteract the increasing sediment load is becoming increasingly urgent especially in the Ethiopian highlands where the construction of the hydroelectric Grand Renaissance Dam on the Blue Nile is underway. In this paper, we examine the results of 9 years of a watershed experiment in which discharge and sediment los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 128 publications
(340 reference statements)
3
47
0
Order By: Relevance
“…subfactor value for stone bunds with trenches installed in rangeland increased from 0.03 in 2010 to 0.12 in 2012 (Figure c). These results are in line with the findings of Guzman et al (), who applied the parameter‐efficient distributed model to estimate the long‐term (9 years) impact of Fany‐juu (throw uphill) bunds on sediment concentration at the outlet of a small experimental catchment in the central Ethiopian Highlands. Their results also indicate that the effectiveness of these SWC structures declines over time and is negligible after 5 years.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…subfactor value for stone bunds with trenches installed in rangeland increased from 0.03 in 2010 to 0.12 in 2012 (Figure c). These results are in line with the findings of Guzman et al (), who applied the parameter‐efficient distributed model to estimate the long‐term (9 years) impact of Fany‐juu (throw uphill) bunds on sediment concentration at the outlet of a small experimental catchment in the central Ethiopian Highlands. Their results also indicate that the effectiveness of these SWC structures declines over time and is negligible after 5 years.…”
Section: Resultssupporting
confidence: 90%
“…This forms a major bottleneck for soil erosion prediction and understanding impacts of natural resource management in Ethiopia and many other developing countries (Karamage et al, ; Mati et al, ; Nigussie et al, ; Nyssen et al, ; Sonneveld, Keyzer, & Albersen, ). A further challenge is that, although several studies show that commonly applied SWC measures such as stone bunds and trenches are highly effective (Desta et al, ; Nyssen et al, , ; Taye et al, ), their effectiveness can also strongly decline over time, due to a decline in static storage capacity (SSC; Guzman et al, ; Taye et al, ). Evaluations of the effectiveness of SWC measures should bring this temporal variability into account.…”
Section: Introductionmentioning
confidence: 99%
“…The NPV is determined assuming that the harvested annual mass of grass from the treated gullies (Table 1) is the same over a seven-year period. This period was selected because soil and water conservation practices last approximately seven years before they become ineffective [32]. A 5% discount rate (interest rate) was used, which is equal to the current deposit rate of the Commercial Bank of Ethiopia.…”
Section: Profitability Of Stabilizing Gulliesmentioning
confidence: 99%
“…The infiltration furrows with bunds were built along the contour across the sloping lands to decrease runoff by reducing or stopping the overland flow and increasing the infiltration of rainwater into the soil in the furrows. Note that due to erosion and filling up of the furrows, most of these practices are only effective for approximately five years [30]. Enclosures are areas closed for free grazing and cultivation, commonly found on degraded marginal lands not suitable for crop cultivation and in valley bottoms where gullies are being formed.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Studies outside the Lake Tana basin found that infiltration furrows decreased direct runoff and sediment load but not sediment concentrations in the first three years of observation when gullies were present [23,28,29]. Another study 200 km south of Lake Tana [30] found that the long-term impact of conservation practices was minimal. None of these studies related the effectiveness of the conservation practices to watershed characteristics.…”
Section: Introductionmentioning
confidence: 99%